Exhumation of the Panama basement complex and basins: Implications for the closure of the Central American seaway. (20th May 2016) - Ramírez, Diego A.; Foster, David A.; Min, Kyoungwon; Montes, Camilo; Cardona, Agustín; Sadove, Gephen
Abstract: The emergence of the Central American isthmus occurred episodically from Eocene to Pliocene time and was caused by a series of tectonic and volcanic processes. Results from zircon U‐Pb geochronology, zircon (U‐Th)/He (ZHe) and apatite (U‐Th)/He (AHe) thermochronology, and zircon Lu‐Hf isotopic data from sedimentary (sandstones and recent river sands) and plutonic rocks from the Azuero Peninsula and Central Panama document the exhumation and uplift history of the Panamanian basement complex. Our data support previous paleobotanical and thermochronological studies that suggest that by middle Eocene time some areas of Central Panama and Azuero Peninsula were exposed above sea level as a series of islands surrounded by shallow open marine waters. The Gatuncillo, Cobachón and Tonosí formations were deposited during this partial emergence. Transtension in the Oligocene‐early Miocene produced various pull‐apart basins (e.g., the Canal Basin) and local uplift that exhumed the Eocene strata (Gatuncillo and Cobachón formations). This event probably reduced circulation between the Pacific Ocean and the Caribbean Sea. The Tonosí Formation records late Miocene to Pleistocene cooling and exhumation, which may be related to uplift above the subducting Coiba Ridge. These results suggest that the emergence of the Isthmus of Panama followed a series of diachronous events that led to the final closure of the Central American seaway. Key Points: Exhumation of the plutonic rocks of the Azuero Marginal complex started in the early/middle Oligocene The Hf isotopic data suggest an island arc origin for the Panamanian basement complex The emergence of the Isthmus of Panama followed a series of diachronous events before the final closure of the Central American seaway